The Concept of Freedom in Contemporary Belarusian Poetry: Based on the Project “Radio Svabody” Верш на свабоду (Poem for Freedom) - Kowalow, Siergiej (Porównania, 2024)
The article is devoted to the reflection of the theme of freedom in contemporary Belarusian poetry based on the material of the unique project “Radio Svaboda” Poem for Freedom. Every day during 2001, a new author’s “poem for freedom” was broadcast on Radio Svaboda, and in 2002, all 365 poems were published as a separate book. The anthology Poem for Freedom reflects the collective perception of freedom in Belarusian society at the beginning of the new millennium. If in the poems of older poets, both professional writers and amateurs, freedom is unequivocally associated with the state independence of Belarus from Russia, with the liberation of Belarusian society from the political dictatorship of Alexander Lukashenko, then in the texts of younger Belarusian poets, as well as in the work of their peers from democratic countries Europe, the problems of individual freedom, responsibility for freedom in the post-industrial society are more clearly raised. At the same time, the anthology Poem for Freedom reflects important trends in the development of Belarusian poetry in the late 20th and early 21st centuries: 1) politicization and ideologising of poetry, turning it into poetic journalism (in the works of older authors), 2) de-ideologizing the artistic text, saturating it with postmodern irony, transforming text in performance (in the works of younger authors)